2020
DOI: 10.1016/j.injury.2020.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Time to intravenous antibiotic administration (TIbiA) in severe open tibial fractures: Impact of change to national guidance

Abstract: Introduction Severe open tibial fractures are limb-threatening injuries. Outcomes depend on a complex interplay of patient, injury and treatment factors. 2009 guidelines from the British Orthopaedic Association (BOA) and British Association of Plastic, Reconstructive and Aesthetic Surgeons (BAPRAS) recommend prophylactic intravenous antibiotic administration within three hours of injury. More recent National Institute for Health and Care Excellence (NICE) 2016 guidelines recommend pre-hospital antibiotic admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…Details about the selection process are outlined in the owchart [Figure 1]. Regarding the surgical treatment of lower extremity open fractures, 15 cohort studies [9,[11][12][13][14][15][16][17][18][19][20][21][22][23][24], ve clinical trials [25][26][27][28][29] and eight systematic reviews with meta-analysis [30][31][32][33][34][35][36][37][38] were included. About the role of the negative pressure wound therapy (NPWT), ve cohort studies [39][40][41][42][43], seven clinical trials [10,[44][45][46][47][48][49] and three systematic reviews with meta-analysis [50][51][52] were included.…”
Section: Resultsmentioning
confidence: 99%
“…Details about the selection process are outlined in the owchart [Figure 1]. Regarding the surgical treatment of lower extremity open fractures, 15 cohort studies [9,[11][12][13][14][15][16][17][18][19][20][21][22][23][24], ve clinical trials [25][26][27][28][29] and eight systematic reviews with meta-analysis [30][31][32][33][34][35][36][37][38] were included. About the role of the negative pressure wound therapy (NPWT), ve cohort studies [39][40][41][42][43], seven clinical trials [10,[44][45][46][47][48][49] and three systematic reviews with meta-analysis [50][51][52] were included.…”
Section: Resultsmentioning
confidence: 99%
“…The average prevalence of GAIIIB fractures was 28.4% in 2000-2009 and 25.1% in 2010-2022, with no significant differences between the periods 1,5,7,12,13,15,17,[19][20][21][22][23][24][25] .…”
Section: Gaiiib (Fig 3 Table 3)mentioning
confidence: 87%
“…However, the evidence reported by You et al in 2020 recommends that the first debridement be performed within 24 h of injury 33) . Hendrickson et al examined infection rates in 112 patients admitted to 4 major trauma centers, of whom 38% (n = 44) received primary debridement within 12 h and 90% within 24 h. The incidence of infectious complications with debridement before and after 12 hours was 4.5 vs. 5.6%, respectively, with no significant difference between the two groups 25) . Rymer et al reported that 84 patients with open leg fractures were referred to university hospitals, and 83 (98.8%) underwent initial debridement within 24 h. Of these, half underwent their first surgery outside normal working hours 34) .…”
Section: Delayed Initial Debridementmentioning
confidence: 99%
“…Treatment of open tibial fractures includes appropriate and prompt antibiotic treatment (within three hours), 22 , 23 surgical debridement, irrigation, bone stabilization, and fast and sufficient soft-tissue coverage. 24 When considering the high infection rates, the diversity of the encountered bacteria and the devastating consequences, e.g.…”
Section: Discussionmentioning
confidence: 99%